Causal Relationships and Reading Comprehension in Science Texts Among Pre-service Teachers - Torres-Merchán, Nidia Yaneth (2026)
Objective. This study analyzes the influence of different levels of academic training in students enrolled in the undergraduate program in Natural Sciences and Environmental Education when reading physics and chemistry texts that contain causal relations. Methodology. This research corresponds to an ex post facto, descriptive study in which an instrument was provided containing three physics and chemistry texts used by full-time faculty members in their courses. These texts included questions on causal relations. A total of 65 students from the first, sixth, and eighth semesters participated, selected through non‑probabilistic convenience sampling. Results. Differences were found among the three groups of readers regarding their ability to establish causal relations and the impact of these relations on textual comprehension, as well as on strategic text processing. An influence of prior knowledge was identified when establishing causal relations among more experienced students, along with difficulties in associating them with preceding sentences. Novice students employed strategic processing through careful reading, which supported text interpretation and meaning-making. Conclusions. Novice students tend to adopt a fragmented approach, whereas more experienced students use strategies aimed at constructing meaning. The study revealed greater ease in understanding chemistry texts compared to physics texts and highlighted the need to introduce exercises involving causal relations from the earliest semesters.